The impact of concentrated flow and slope on unpaved loess‐road erosion on the Chinese Loess Plateau. (4th October 2020) - Guo, Wenzhao; Bai, Yun; Cui, Zhiqiang; Wang, Wenlong; Li, Jianming; Su, Zhengan
Abstract: Loess‐roads (LR) still experience severe soil erosion due to concentrated flow during rainstorms in watersheds on the Chinese Loess Plateau, where soil erosion in sloping farmland, abandoned land, and grassland has been controlled. However, road erosion is commonly overlooked because unpaved roads represent a small part of the catchment area. In situ scouring‐erosion experiments were performed on LR surfaces in the Liuaogou watershed on the Loess Plateau. The erosion rate of the LR was 14.1–234.6 g m −2 min −1, which is 10.8–57.5‐times higher than that on an adjacent grassy hillslope. In most experiments, the LR erosion rate generally increased linearly with increasing concentrated flow and slope gradient ( R 2  > .85; significance p  < .05). Concentrated flow had a greater impact on road erosion than the road surface slope. Rill erosion occurred in our road plots, with rill area densities of 0.03–0.38 m 2 m −2 . The total amount of road erosion was significantly correlated linearly with the rill area density ( R 2 = .61, p  < .01), indicating that high rill density led to high total erosion on the LR. A road erosion equation based on concentrated flow and slope gradient was established and validated. The R 2, p, and NSE results were .91, <.01 and 0.93, respectively, implying that the fitted equation can be considered acceptable. Our findings can provide references for the prevention of road erosion and the establishment of road erosion models.